Social Science Learning Model for Early Childhood Based on Digital Wayang Golek to Enhance Social Awareness - Hurri, Ibnu; Abidin, Rahman; Wirawan, Gandung (JURNAL PENDIDIKAN USIA DINI, 2026)
This research seeks to create and evaluate the efficacy of a social studies learning model for early childhood education (PAUD) rooted in local wisdom through digital puppetry to enhance social awareness in young children. This methodology aims to include Sundanese cultural values using puppet figures and narratives delivered in an interactive digital format. The study employs a Research and Development (R&D) methodology encompassing needs analysis, model creation, expert validation, and both restricted and large field testing. We gathered data through observation, interviews, documentation, and analysis of children's prosocial behavior during the educational process. The study's findings reveal that using digital puppets significantly improves children's ability to demonstrate empathy, share, support peers, collaborate, and resolve minor conflicts. Educators appreciate the ease of conveying social studies content that was once abstract, since digital media facilitates the presentation of a tangible and engaging social context. The digitization of wayang golek has demonstrated its efficacy in revitalizing indigenous wisdom while addressing the demand for technology-based education in early childhood development (PAUD). This study highlights that the amalgamation of culture and technology in social studies learning is a relevant strategy to build children's social character from an early age.